2019
DOI: 10.4049/jimmunol.1801382
|View full text |Cite
|
Sign up to set email alerts
|

Low Cellular NAD+ Compromises Lipopolysaccharide-Induced Inflammatory Responses via Inhibiting TLR4 Signal Transduction in Human Monocytes

Abstract: This information is current as Transduction in Human Monocytes Responses via Inhibiting TLR4 Signal Lipopolysaccharide-Induced Inflammatory Compromises + Low Cellular NAD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
(34 reference statements)
2
26
1
Order By: Relevance
“…Moreover, adding NAD + to cultured macrophages increased M2 polarization and the expression levels of IL‐1ra and IL‐10, which are anti‐inflammatory (with no effect on M1). Somewhat consistent with these findings are the recent observations that intracellular NAMPT and NAD + appear to be necessary for activation of the major protein component of the inflammasome (NLRP3) of human primary monocytes, which are precursors of macrophages 163 . Their contribution was attributed to the maintenance of TLR4 signal transduction, which is critical as a priming signal for the NLRP3 inflammasome, specifically their importance for TLR4‐induced phosphorylation of several downstream proteins in the MyD88‐dependent signal pathway.…”
Section: The Relationship Between Nad Levels Enzymes Synthesizing Orsupporting
confidence: 65%
“…Moreover, adding NAD + to cultured macrophages increased M2 polarization and the expression levels of IL‐1ra and IL‐10, which are anti‐inflammatory (with no effect on M1). Somewhat consistent with these findings are the recent observations that intracellular NAMPT and NAD + appear to be necessary for activation of the major protein component of the inflammasome (NLRP3) of human primary monocytes, which are precursors of macrophages 163 . Their contribution was attributed to the maintenance of TLR4 signal transduction, which is critical as a priming signal for the NLRP3 inflammasome, specifically their importance for TLR4‐induced phosphorylation of several downstream proteins in the MyD88‐dependent signal pathway.…”
Section: The Relationship Between Nad Levels Enzymes Synthesizing Orsupporting
confidence: 65%
“…Evidence shows that elevated levels of intracellular NAD + enhance IL-1β secretion. Additionally, this study found that sirtuin inhibition did not suppress NLRP3 inflammasome activity, and low levels of NAD + were found to inhibit IL-1β secretion [130]. Further investigation into this discrepancy is needed.…”
Section: Acetylation and Nad Cyclingmentioning
confidence: 78%
“…More recently, the same group that firstly identified TLR4 as NAMPT receptor published new details about this interaction (155). At the same time, a direct role of NAD in activating the inflammasome was recently reported by Yang et al The authors demonstrated that NAD manipulation, using NAMPT inhibitors or the treatment with NAD precursors, affects TLR4-mediated NF-κB activation and PYD-domain 3 (NLRP3) inflammasome activity connecting intracellular NAD levels and inflammation (156).…”
Section: Enampt/enaprt In Myeloid Cells Function: the Role Of Tlr4mentioning
confidence: 95%